Preservation of the IFPRI record: Moving 50 Years of research - Plummer, Leigh; Miller, Ryan; Yerramareddy, Indira (American Library Association, 2025)
As the International Food Policy Research Institute approaches a half-century of agricultural research, the Communications Unit has taken the opportunity to review the legacy of both our organization and our researchers. As part of this effort, the Knowledge Management team spent a year migrating over 25,000 metadata records, including about 13,000 with a PDF file attached, from an Institutional Repository (CONTENTdm) to a shared Consortial Repository (CGSpace based on DSpace). In the process, we have improved the metadata and worked to conform our records with the different standards of the shared environment and ensure continued discoverability and usability. We were also able to identify key gaps in our open access holdings and added PDF files were possible. We continue to validate the metadata and holdings, including additions of chapter records that were previously missing. Our project has led to a greater role for our team on the shared platform and we have trained other CGIAR centers on how to successfully migrate their collections.